Comparative analysis of corpus callosum lipidome and transcriptome in schizophrenia and healthy brain - Maria S. Osetrova; Olga I. Efimova; Marina D. Zavolskova; Elena A. Stekolschikova; Gleb N. Vladimirov; Dmitry A. Senko; Tatiana A. Zhuravleva; Anna Y. Morozova; Yana A. Zorkina; Denis S. Andreyuk; George P. Kostyuk; Evgeniy N. Nikolaev; et al. (Consortium Psychiatricum)
BACKGROUND: Functional and structural studies of the brain highlight the importance of white matter alterations in schizophrenia. However, molecular studies of the alterations associated with the disease remain insufficient.